2011
DOI: 10.1203/pdr.0b013e318225f748
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Culture of Fibroblasts, Vascular Smooth Muscle, and Endothelial Cells From the Fetal Rat Ductus Arteriosus

Abstract: ABSTRACT:The ductus arteriosus (DA), a fetal arterial shunt vessel between the proximal descending aorta and the pulmonary artery, closes shortly after birth. Initial functional closure as a result of the DA's smooth muscle contraction is followed by definite anatomical closure. The latter involves several complex mechanisms like endothelial cushion formation and smooth muscle cell migration resulting in fibrosis and sealing of the vessel. These complex steps indicate highly specialized functions of the DA vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…We hypothesized that the ECs of the DA exhibit a unique gene profile involved in DA-specific vasoconstriction and vascular remodeling. Recently, Weber et al reported that they successfully isolated ECs from fetal rat DA using the immunomagnetic cell separation method and harvested the isolated ECs to further confirm their purity by flow cytometry analysis [12]. In the present study, we investigated gene expression differences in ECs between the DA and the aorta by using a combination of fluorescence-activated cell sorter (FACS) and DNA microarray experiments followed by further enrichment analysis using MetaCore GeneGo software.…”
Section: Introductionmentioning
confidence: 97%
“…We hypothesized that the ECs of the DA exhibit a unique gene profile involved in DA-specific vasoconstriction and vascular remodeling. Recently, Weber et al reported that they successfully isolated ECs from fetal rat DA using the immunomagnetic cell separation method and harvested the isolated ECs to further confirm their purity by flow cytometry analysis [12]. In the present study, we investigated gene expression differences in ECs between the DA and the aorta by using a combination of fluorescence-activated cell sorter (FACS) and DNA microarray experiments followed by further enrichment analysis using MetaCore GeneGo software.…”
Section: Introductionmentioning
confidence: 97%
“…These microarray studies looked at a mixed cell population. In the future, a more refined approach may be to perform transcriptional profiling using specific cell populations such as smooth muscle cells, endothelial cells and fibroblasts [71] to gain insight into cell-specific mechanisms of DA development and function.…”
Section: Genetic Considerations In Pda Pathobiologymentioning
confidence: 99%
“…Although several molecular pathways (eg, nitric oxide, vascular endothelial growth factor, the cyclooxygenase [COX]/prostaglandin system [8][9][10][11] ) are known to be involved in permanent DA sealing, the complex cellular and molecular mechanisms contributing to DA closure remain poorly understood. 12 Intriguingly, Echtler et al 13 reported that platelet-triggered ductal sealing (with subsequent vascular remodeling) seems to be an important mechanism for definite DA closure. In their mouse models, platelets were recruited to the endothelium of the DA soon after birth, and induced platelet dysfunction or defective platelet formation resulted in persistent PDA.…”
mentioning
confidence: 99%